Effects of Digital Storytelling-Aided Instruction on Students' Narrative Writing and Speaking Skills - Eva Riani; Husnawadi Husnawadi; Syarifudin Syarifudin (Universitas Islam Negeri (UIN) Mataram, 2021)
Although Digital Storytelling (DST) has been widely and recently applied and studied in ELT classrooms, little research has documented its efficacy towards narrative writing and speaking skills. For this reason, this quasi-experimental research aimed to investigate its effects when used as a medium of learning on students' narrative writing and speaking skills at an Indonesian privately owned Islamic school. A total of 42 participants were divided into two groups: experimental and control groups. The data collected through pre-and post-writing and oral tests were analyzed using the independent t-test formula in SPSS 20. The statistical evidence showed that the students in the experimental groups significantly outperformed their counterparts in the control group in terms of narrative writing skills given t(19) -12.02, p= 0.000. However, another statistical evidence indicated that the narrative speaking skills of both groups were not significantly different given t(19)-2.02 and p-value= 0.057. This study further discusses its limitations and implications for the effective deployment of DST in EFL classrooms.